Dexamethasone-Loaded Thermosensitive Hydrogel Suppresses Inflammation and Pain in Collagen-Induced Arthritis Rats - Wang QS; Xu BX; Fan KJ; Li YW; Wu J; Wang TY (Dove Medical Press, 2020)
Qi-Shan Wang,* Bing-Xin Xu,* Kai-Jian Fan, Yun-Wu Li, Jing Wu, Ting-Yu Wang Departments of Pharmacy, Shanghai Ninth People’s Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this work.Correspondence: Ting-Yu Wang Email drtywang@163.comPurpose: To overcome negative adverse effects and improve therapeutic index of dexamethasone (Dex) in rheumatoid arthritis (RA), we developed a novel sustained release formulation-intra-articular injectable dexamethasone-loaded thermosensitive hydrogel (DLTH) with chitosan-glycerin-borax as carrier for the remission of inflammation and pain. The focus of this article is to explore both anti-inflammatory and pain-relieving effects of DLTH joint injection in bovine type-II collagen-induced arthritis (CIA) rats.Methods: Wistar rats were randomized into three groups, including the normal group (n=6), the model group (n=6) and the DLTH group (n=10). Joint injection of DLTH (1mg/kg Dex per rat) was injected on day 12 in the DLTH group twice a week for three weeks. Clinical signs of body weight, paw swelling and arthritis scores, histologic analysis, hind paw mechanical withdrawal threshold (MWT), plantar pressure pain threshold (PPT) were taken into consideration. Serum contents of IL-17A, prostaglandin E2 (PGE2), prostacyclin 2 (PGI2) and prostaglandin D2 (PGD2), real-time polymerase chain reaction (PCR) analysis of inflammatory factors and pain-related mediators in synovium and dorsal root ganglia (DRG), Western blotting of NF-κB in synovium were all evaluated.Results: Paw swelling, arthritis scores and joint inflammation destruction were all attenuated in the DLTH-treated group. Results showed that DLTH not only down-regulated serum IL-17A, but also mRNA levels of inflammatory factors and NGF, and key proteins contents of the NF-κB pathway in synovium. Increases of MWT and PPT in DLTH-treated rats elucidated pain-reducing effects of DLTH. Elevated serum PGD2 levels and declines of serum PGE2 and PGI2, and inflammatory and pain-related genes in DRGs in the DLTH group were also recorded.Conclusion: These data elucidated that DLTH joint injection impeded synovial inflammation processes through down-regulating transcription activity of NF-κB pathway, and intra-articular DLTH may aid in the regulation of RA pain through regulating inflammation and pain conduction process.Keywords: anti-inflammatory, dexamethasone-loaded thermosensitive hydrogel; DLTH, pain-relieving, rheumatoid arthritis; RA